Neural time course of visually enhanced echo suppression - Bishop, Christopher W. (American Physiological Society, 2012)
Auditory spatial perception plays a critical role in day-to-day communication. For instance, listeners utilize acoustic spatial information to segregate individual talkers into distinct auditory “streams” to improve speech intelligibility. However, spatial localization is an exceedingly difficult task in everyday listening environments with numerous distracting echoes from nearby surfaces, such as walls. Listeners' brains overcome this unique challenge by relying on acoustic timing and, quite surprisingly, visual spatial information to suppress short-latency (1–10 ms) echoes through a process known as “the precedence effect” or “echo suppression.” In the present study, we employed electroencephalography (EEG) to investigate the neural time course of echo suppression both with and without the aid of coincident visual stimulation in human listeners. We find that echo suppression is a multistage process initialized during the auditory N1 (70–100 ms) and followed by space-specific suppression mechanisms from 150 to 250 ms. Additionally, we find a robust correlate of listeners' spatial perception (i.e., suppressing or not suppressing the echo) over central electrode sites from 300 to 500 ms. Contrary to our hypothesis, vision's powerful contribution to echo suppression occurs late in processing (250–400 ms), suggesting that vision contributes primarily during late sensory or decision making processes. Together, our findings support growing evidence that echo suppression is a slow, progressive mechanism modifiable by visual influences during late sensory and decision making stages. Furthermore, our findings suggest that audiovisual interactions are not limited to early, sensory-level modulations but extend well into late stages of cortical processing.